Development of a cold storage facility for agricultural produce using air conditioner - Kumar, Sanoj; Kumar, Ashok; Kumar , Satish (Journal of Postharvest Technology, 2019)
Although mechanical refrigeration is the best technology for coolrooms and transportation systems, Conventional reefers are economically and practically infeasible for limited resource farmers. In present work, a device CoolBot” was tested along with selection of low cost insulation technology. CoolBot is a device, which turns a conventional room air conditioner into a produce cooler. The air conditioner thermostat is heated so that the unit keeps running until the room temperature reaches the CoolBot set point. To prevent icing of the fins, the CoolBot measures the fin temperature and stops the compressor (through the thermostat heater) when ice builds up. The ice on the fins continues to cool the room air until it melts and the compressor turns on again. The developed setup can go close to 00 C of room temperature within 2 hour of running